Impact of TCSC control methodologies on subsynchronous oscillations. - Pilotto, L.A.S (IEEE Transactions on power delivery)
This paper presents a detailed analysis of the impact of different TCSC control methodologies on subsynchronous oscillations problem of series capacitive compensated transmission systems. The first IEEE benchmark model for the analysis of SSR phenomena is adopted. The system was evaluated for several different compensation levels. Three different control methodologies were checked, namely: constant current, constant power, and constant impedance control. The influence of ratings and the impact of different firing control methodologies are also evaluated.